Bioethics and the Mission of Philosophy (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The research seeks to investigate the concept of bioethics and its principal definitions. It also shows its operating mechanisms since it focuses on the various conditions that are required to lead the human life in the context of the rapid and complex developments of human knowledge and biomedical techniques. Besides, it attempts to follow the conflicts among scientists regarding the moral validity for the synthesis of molecular cells, genome, human reincarnation, genealogy and embryology in order to establish a criterion for human behavior which can be acceptable in domains of life and death equally. In addition to that, we aim in this respect to examine the role and function that philosophy performs when it broadens the scope of its work and expands to the limits of various knowledge fields to draw its goals and aims in a way that suits the human dignity which people aspire regardless of their beliefs and views.